A Novel Methodology for the Asymmetric Synthesis of 2,3,5-Trisubstituted Piperazine Derivatives - Beksultanova, Nurzhan; Özdemir, Özge; Çakır, Sıdıka Polat; Aygün, Muhittin; Doğan, Özdemir (Synthesis, 2024)
Piperazines constitute an important structural feature of many pharmaceuticals. For the discovery of new drugs, the ability to modify the lead compound’s structure is crucial. Herein, we provide an efficient method for the synthesis of chiral 2,3,5-trisubstituted piperazine structures. Our route enables the synthesis of several novel chiral aryl aziridinyl ketones that could be converted into aziridine-fused bicyclic imines. The reduction of these imines and the nucleophilic ring-opening reaction of the aziridine ring allowed us to synthesize highly functionalized piperazine derivatives.
Keywords: piperazines; asymmetric synthesis; aziridines; Staudinger reaction; intramolecular cyclization